An examination of individual responses to ischemic preconditioning and the effect of repeated ischemic preconditioning on cycling performance - Slysz, J. T.; Petrick, H. L.; Marrow, J. P.; Burr, J. F. (European Journal of Sport Science, 2020)
Purpose: To use repeated control trials to measure within-subject variability and assess the existence of responders to ischemic preconditioning (IPC). Secondly, to determine whether repeated IPC can evoke a dosed ergogenic response. Methods: Twelve aerobically fit individuals each completed three control and three IPC 5-km cycling time trials. IPC trials included: (i) IPC 15-min preceding the trial (traditional IPC), (ii) IPC 24-h and 15-min preceding (IPC × 2), (iii) IPC 48-h, 24-h, and 15-min preceding (IPC × 3). IPC consisted of 3 × 5-min cycles of occlusion and reperfusion at the upper thighs. To assess the existence of a true response to IPC, individual performance following traditional IPC was compared to each individual`s own 5-km TT coefficient of variation. In individuals who responded to IPC, all three IPC conditions were compared to the mean of the three control trials (CONavg) to determine whether repeated IPC can evoke a dosed ergogenic response. Results: 9 of 12 (75%) participants improved 5-km time (-1.8 ± 1.7%) following traditional IPC, however, only 7 of 12 (58%) improved greater than their own variability between repeated controls (true responders). In true responders only, we observed a significant mean improvement in 5-km TT completion following traditional IPC (478 ± 50 s), IPC × 2 (481 ± 51 s), and IPC × 3 (480.5 ± 49 s) compared to mean CONavg (488 ± 51s; p < 0.006), with no differences between various IPC trials (p > 0.05). Conclusion: A majority of participants responded to IPC, providing support for a meaningful IPC-mediated performance benefit. However, repeated bouts of IPC on consecutive days do not enhance the ergogenic effect of a single bout of IPC.